The effect of corporate governance, leverage, and liquidity on islamic social reporting (ISR) disclosure in islamic commercial banks in Indonesia - Dinna Riyani; Nurul Hasanah Uswati Dewi (STIE Perbanas Surabaya, 2018)
Islamic Social Reporting is the standard index of performance reporting in sharia-based companies. This index was born on the basis of reporting standards based on AAOIFI (Accounting and Auditing Organization for Islamic Financial Institutions). The objective of this research was to knowing the extent of Corporate Governance, leverage dan liquidity of Islamic Social Reporting Disclosure (ISR). The independent variables were used in this study is The Board of Comisionner, The Board of Directors, The Audit Comitte, Sharia Supervisory Boad, leverage and liquidity, while the dependent variable is the ISR disclosure. Samples were taken by using census sampling technique. The final sample as many as 12 islamic bank in Indonesia on 2012-2016. Data analysis method of the data used in this research is descriptive analysis, classical assumption test, and multiple linear regression using SPSS 23 for windows. The results of this study showed that The Board of Comisionner and liquidity has effect ISR disclosure. The Board of Directors, The Audit Comitte, Sharia Supervisory Boad, leverage does not affect the ISR disclosure.